Effect of COVID-19 on Rural Economy at Eastern Terai of Nepal - Timsina, Tirtha Raj (Rupantaran: A Multidisciplinary Journal, 2020)
This article aims to find out the effect of COVID-19 pandemic in rural agricultural economy. It is descriptive research so that the findings has tried to objectively described based on field survey the on the effects of pandemic at Pathari Shanishchare Municipality of Morang district situated in eastern Terai of Nepal. Rural economy of Nepal is primarily constituted by the dominance of agriculture and allied sectors which occupies two third of the domestic subsistence from the long year back. The world currently has passing through the panic effect of COVID-19 pandemic and none of the sectors has left behind from its effect. Evidence reveals that various sectors of Nepalese economy intensely influenced whereas the weaker segments of the society are hardest hit by pandemic. Despite the existence of effect in rural and agriculture sector in particular that has never anticipated, ultimately we are compelled to cope with such type of pandemic if existed anytime ahead. Therefore this study is one of the representative studies of the effect of pandemic through which rural people in general and the agricultural sectors in particular would be able to adapt the appropriate action plan in future. The study shows that the physical effect of this pandemic is comparatively lower but psychologically greater in nature. So the agriculture would be the better option to utilize surplus time and resources so that rural community as well as entire nation could cope with.